Detubularized Ureterosigmoidostomy for the Creation of Continent Neobladder in Children: Cases Report and Review of the Literature - Edoardo Bindi; Michele Ilari; Giovanni Torino; Francesca Mariscoli; Fabiano Nino; Giovanni Cobellis; Ascanio Martino (MDPI AG, 2021)
Introduction: To report our experience in continent urinary diversions, we describe two cases we treated performing detubularized ureterosigmoidostomy. In children, in the case of malformations or neoplastic diseases affecting the bladder, the need for a cystectomy is not so frequent. When cystectomy becomes mandatory, there is a need to create a continent bladder diversion. Mainz pouch II and Cologne pouch are procedures that utilize a detubularized sigma as a reservoir in order to build up a continent neo-bladder. Materials and methods: This is a retrospective study performed at the Pediatric Surgical Unit of the Salesi Children's Hospital. In this work, we reviewed data about two patients who underwent surgery for the creation of a sigmoid neo-bladder by the Mainz pouch II and Cologne pouch techniques. Results: In our experience, we treated a girl who was affected by a bladder's rabdomiosarcoma and a girl born with a bladder exstrophy and treated at birth abroad. In both patients, a complete cystectomy was performed and a continent neo-bladder was created by a detubularized ureterosigmoidostomy. In the first case, we performed the Mainz pouch II technique and in the second, the Cologne pouch technique. Discussion: Different techniques have been developed with the main goal of the creation of an orthotopic neo-bladder, which has to be a low pressure reservoir with a continent sphincteric mechanism. Detubularized ureterosigmoidostomy is a good choice in pediatric patients. Our study, according to other works, shows that these procedure are safe with good long-term outcomes.